Insight into the evolution of the histidine triad protein (HTP) family in Streptococcus. - Zhu-Qing Shao (Public Library of Science (PLoS), 2013)
The Histidine Triad Proteins (HTPs), also known as Pht proteins in Streptococcus pneumoniae, constitute a family of surface-exposed proteins that exist in many pathogenic streptococcal species. Although many studies have revealed the importance of HTPs in streptococcal physiology and pathogenicity, little is known about their origin and evolution. In this study, after identifying all htp homologs from 105 streptococcal genomes representing 38 different species/subspecies, we analyzed their domain structures, positions in genome, and most importantly, their evolutionary histories. By further projecting this information onto the streptococcal phylogeny, we made several major findings. First, htp genes originated earlier than the Streptococcus genus and gene-loss events have occurred among three streptococcal groups, resulting in the absence of the htp gene in the Bovis, Mutans and Salivarius groups. Second, the copy number of htp genes in other groups of Streptococcus is variable, ranging from one to four functional copies. Third, both phylogenetic evidence and domain structure analyses support the division of two htp subfamilies, designated as htp I and htp II. Although present mainly in the pyogenic group and in Streptococcus suis, htp II members are distinct from htp I due to the presence of an additional leucine-rich-repeat domain at the C-terminus. Finally, htp genes exhibit a faster nucleotide substitution rate than do housekeeping genes. Specifically, the regions outside the HTP domains are under strong positive selection. This distinct evolutionary pattern likely helped Streptococcus to easily escape from recognition by host immunity.